Perinatal and neonatal morbidity among infants of diabetic mothers at a university hospital in Central Saudi Arabia - Al-Nemri, Abdulrahman M. (Saudi Med J, 2018)
OBJECTIVES: To determine the perinatal and neonatal morbidity related to diabetes associated with pregnancy. METHODS: This is a prospective cohort study conducted at a tertiary university hospital in Central Saudi Arabia. All neonates born to mothers with pregnancy associated diabetes between July 2014 and June 2015 were recruited for the purpose of this study. Infants born at 23 weeks or less, infants who died within 3 hours of delivery, twins, and unbooked pregnant ladies were excluded from the study. RESULTS: A total of 279 ladies and 289 infants were enrolled in the study. Gestational diabetes was observed in 84.5% of study subjects, type 1 diabetes in 2.8%, and type 2 diabetes in 12.5% of the females that were examined. A variety of neonatal complications were observed in infants of diabetic mothers including macrosomia, hypoglycemia, hypocalcemia, hyperbilirubinemia, respiratory distress syndrome, and congenital malformations. Macrosomia, hypoglycemia, respiratory distress syndrome, and NICU admission correlate with poor control of diabetes during pregnancy (HbA1c >7%). Moreover, the presence of congenital malformations correlates with poor diabetes control in the first and second trimester, but not in the third trimester. CONCLUSION: Infants of diabetic mothers in this cohort developed a variety of neonatal events that largely correlates with poor metabolic control during pregnancy.